A review of the conduct of Malaysia monetary policy between 1959 and 1992 / Goy Siew Ching (Universiti Teknologi MARA, Sarawak, 1996)
Monetary Policy is part of the economic policy of a country. It is used to achieve the basic goals of the economic policy. The principal macroeconomic objective of the monetary policy in Malaysia is to promote the highest sustainable rate of output growth while maintaining low domestic price and stable exchange rate. Monetary stability has always been considered a key prerequisite for sustained growth. In working towards this objective, the Central Bank has to ensure that growth in both bank credit and money supply is adequate to accommodate and fuel real growth in the economy, without causing inflationary pressure.